MiR-199-3p promotes ERK-mediated IL-10 production by targeting poly (ADP-ribose) Polymerase-1 in patients with systemic lupus erythematosus. (1st June 2019) - Su, Xiaoping; Ye, Lele; Chen, Xinxin; Zhang, Huidi; Zhou, Ying; Ding, Xiaokai; Chen, Dan; Lin, Qiaoai; Chen, Chaosheng
Abstract: MicroRNAs (miRNAs) have been implicated in both biological and pathological processes in patients with systemic lupus erythematosus (SLE). Previous studies have demonstrated dysregulated expression of miR-199-3p, interleukin (IL)-10, and poly (ADP-ribose) polymerase-1 (PARP-1) in SLE. However, the underlying mechanisms of these aberrations have not been fully elucidated. In this study, we investigated the mechanism through which miR-199-3p dysregulation contributed to the pathogenesis of SLE. Altered gene expression was assessed by ChIP analysis. We then silenced the expression of candidate genes using siRNA for functional analysis; mRNA expression, protein levels, and protein expression were determined by qRT-PCR, ELISA, and western blotting, respectively. According to ChIP and qRT-PCR results, miR-199-3p was up-regulated in SLE patients. Moreover, IL-10 was found to be highly expressed in SLE patients by ELISA. Further, PARP1 was significantly down-regulated in SLE patients based on western blotting. Our results also indicated that miR-199-3p inhibits PARP1 expression by activating the ERK1/2 pathway, thereby increasing IL-10 expression. Significantly up-regulated miR-199-3p was inversely related to PARP-1 expression and positively correlated with IL-10 levels in SLE. As miR-199-3p was shown to target PARP-1 to activate the ERK1/2 pathway and promote IL-10 production, restoring physiological miR-199-3p levels could represent a potential therapeutic strategy for SLE treatment. Highlights: miR-199-3p is up-regulated in systemic lupus erythematosus (SLE) patients. IL-10 is highly expressed and PARP1 is significantly down-regulated in SLE patients. miR-199-3p down-regulates PARP1 via the ERK1/2 pathway, increasing IL-10 levels. miR-199-3p inversely related to PARP-1 and positively correlated with IL-10 in SLE.